Rational Choice of Students in Determining Careers to Become Esport Athletes in UNS Esports Community (UNSEC) Athletes - Rangga Dwi Kristanto*; Danang Purwanto (Universitas Syiah Kuala, 2024)
This study aims to explore the rational choice of UNSEC Athletes to pursue a career as an esports athlete. These conditions are then analyzed using the theory of rational choice by James S. Coleman. This research uses a qualitative method with a descriptive analysis approach. Research informants were selected using purposive sampling technique with certain criteria, including UNSEC students who have been athletes for at least 1 year. Data were collected using interviews, observation, and documentation. The data that has been collected is then analyzed using interactive analysis techniques by Miles and Huberman. The research results indicate that UNSEC students choose to pursue a career as esports athletes based on their high interest in online games from a young age. They are confident that esports will continue to evolve, which makes them interested in pursuing a career in this field. Additionally, they have confidence in their ability to compete with other athletes. This confidence is supported by various resources they possess, such as advanced devices, parental support, and the UNSEC community. According to the theory of rational choice, UNSEC students as actors are able to manage the resources they have, such as devices that meet the needs of athletes in competition, parental support that is beginning to show acceptance of their career choice, and the relational facilities and location provided by the UNSEC community to enhance the athletes' comfort in competing. This rational background serves as the foundation for UNSEC students to choose a career as esports athletes